Infection Risk Associated with Daratumumab. (4th October 2017) - Johnsrud, Joyce J; Susanibar, Sandra; Jo-Kamimoto, Jorge; Johnsrud, Andrew J; Kothari, Atul; Burgess, Mary J; Schinke, Carolina; Thanendrarajan, Sharmilan; Zangari, Maurizio; Davies, Faith; Morgan, Gareth; Vanrhee, Frits; et al.
Abstract: Background: Daratumumab is an IgG kappa monoclonal antibody (mAB) against CD38 which is expressed on myeloma cells. It has recently been approved for treatment of patients with relapsed refractory multiple myeloma. Our objective was to identify the potential infectious complications associated with daratumumab use. Methods: We conducted a retrospective analysis of myeloma patients who received daratumumab at our institution from October 2015 to December 2016. Patients were divided into four groups based on administration regimen of daratumumab: (1) single agent with dexamethasone; (2) triple therapy with proteasome inhibitor (PI), immune-modulating drug (IMiD), mitogen-activated protein kinase (MEK) inhibitor or mAB; (3) quadruple therapy with IMiD + PI ± mAB or cyclophosphamide; (4) with high-dose chemotherapy. For each group, we evaluated the incidence of infection, neutropenia (defined as ANC <1, 000), hospitalization, and 90-day survival. Results: A total of 171 patients (63% male, 37% female) were included in the study and received a total of 343 cycles of daratumumab. Median age was 68 years. A total of 151 infections occurred in 121 of the 343 cycles (40% bacterial; 52% viral). There was a significant association between development of infection and chemotherapy regimen used (χ 2 = 17, P ≤ 0.001). Patients developed neutropenia in 129 of 254 cycles (51%). There was a significant association between the development of neutropenia and chemotherapy regimen used (χ 2 = 43.51, P < 0.00001). Discontinuation of chemotherapy occurred in 65 cycles (19%), mainly due to progression of disease (54%). Eighty subjects (23%) required hospitalization, infection being the main cause (51%). Ninety-day survival was 91.8%. Conclusion: Infection is common among myeloma patients who receive daratumumab. Myeloma patients who receive daratumumab in conjunction with multidrug chemotherapy regimens have an increased risk of infection and neutropenia. Because daratumumab is given predominantly as outpatient therapy, a greater understanding of the potential immunomodulatory effects of daratumumab will lead to increased vigilance in identifying and treating clinically significant infections. Disclosures: F. Davies, Janssen: Consultant, Speaker honorarium. G. Morgan, Janssen: Consultant and Research Contractor, Research support and Speaker honorarium.